INSPEKSI KESELAMATAN JALAN SYAFRUDDIN PRAWIRA NEGARA KM 7 SAMPAI KM 8 DENGAN METODE HAZARD IDENTIFICATION AND RISK ASSESMENT DI KABUPATEN LIMA PULUH KOTA - Fadhli, Tri; Yermadona, Helga; Endri, Endri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Based on the results of analysis of accident data obtained from the Limapuluh Kota Regency Police in the last 5 years (2018-2022), Jalan Negara Km 7 which is located in Harau District is ranked second in the accident-prone areas in Limapuluh Kota Regency. Jalan Negara Km 7 has a road function, namely a primary artery, so adequate roads and road equipment are needed to improve safety by carrying out road safety inspections and identifying hazards with their risk levels. The road safety inspection method used in this study is to use a road safety inspection form. Hazard identification and risk assessment are carried out using the Australian / New Zealand Standard method, namely by using a risk level matrix. The results of the analysis and discussion in this research show that the traffic lane width is 3.5 M, the left shoulder width is 1 M, the right shoulder width is 1 M, there are no sidewalks and medians, the signs are in 81% good condition, the markings are in 100% good condition, the lighting is public roads with 56% good condition. In the results of hazard identification and risk assessment, it was found that the percentage of high risk level was 40%, the medium risk level was 20%, and the low risk level was 40%. To reduce the potential for accidents and fatality rates, recommendations for handling are made, namely the procurement of damaged and non-existent signs, providing zebra crossings, installing noise tape, and maintaining street lighting and road equipment in hazard locations.Keywords: Road Safety Inspection, Risk, Hazard